2018
DOI: 10.1016/j.foodchem.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in enzymatic activities and functionality of whole wheat flour due to steaming of wheat kernels

Abstract: The effects of steaming wheat kernels on lipolytic degradation of resulting whole flour was studied by quantifying enzyme activities and lipid degradation products during storage. Lipase, lipoxygenase, polyphenol oxidase, and peroxidase activities were decreased by up to 81%, 63%, 22%, and 34%, respectively, as the time of steaming increased up to 90 s. Steaming had no effect on starch and gluten properties. Upon storage free fatty acids decreased with respect to time of steaming. Time of steaming did not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
2
34
0
2
Order By: Relevance
“…The enzyme was mostly in the bran and germ fraction and tempering allowed the moisture to reach inside. The higher reduction in enzyme activities of POD indicated that lipase enzyme was more heat stable than POD enzyme, which was different from the most conclusions reported on wheat and rice (Wu et al ., ; Poudel & Rose, ). Interestingly, peroxidase activity in the hazelnut, with cold‐resistant ability and enduring the harsh winter of −30 °C, could no longer be detected after roasting treatment, while lipase activity could still be detected (Seyhan et al ., ), showing that lipase in both hazelnut and highland barley was insensitive to temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme was mostly in the bran and germ fraction and tempering allowed the moisture to reach inside. The higher reduction in enzyme activities of POD indicated that lipase enzyme was more heat stable than POD enzyme, which was different from the most conclusions reported on wheat and rice (Wu et al ., ; Poudel & Rose, ). Interestingly, peroxidase activity in the hazelnut, with cold‐resistant ability and enduring the harsh winter of −30 °C, could no longer be detected after roasting treatment, while lipase activity could still be detected (Seyhan et al ., ), showing that lipase in both hazelnut and highland barley was insensitive to temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike refined flour which has little bran and germ fractions, the whole flour deteriorates rapidly during storage because of the existence of enzymes in the bran and germ fractions, initiating oxidation and hydrolysis of lipid (Lei et al ., ). Lipase causes hydrolytic rancidity with the release of free fatty acids (FFA) and peroxidase (POD) promotes oxidative rancidity through the oxidation of FFA (Lei et al ., ; Ling et al ., ; Poudel & Rose, ). With the onset of rancidity, poor flavour and nutrients decomposition were raised (Wu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Таким образом, можно сделать вывод, что инновационные технологии позволяют улучшить органолептические показатели хлеба, тем самым повысить его привлекательность для потребителя, но также имеется связь между классом пшеницы и органолептическими свойствами полученных образцов хлеба [6,[8][9][10][11][12].…”
Section: )unclassified
“…Обсуждение В соответствии с проведенным анализом литературных источников [4][5][6][8][9][10][11][12][13][14][15] результаты органолептические, физико-химические свойства хлебных образцов, полученных с применением инновационных технологий из пшеницы разных классов, показали, что кавитационная и ионоозонная обработка оказывают влияние на качество готовых изделий. Вместе с тем можно утверждать, что класс пшеницы оказывает значительное влияние на качество готовых образцов хлеба.…”
Section: )unclassified
“…The limited shelf life of whole‐grain flour, especially as raw material, potentially leads to food lost and food waste. Attempts have been made to deactivate wheat lipases and other esterases through thermal treatment, application of salt solution, and irradiation . These methods, however, not only are energy consuming but may also decrease the nutritional value of the products.…”
Section: Introductionmentioning
confidence: 99%